Using implementation science frameworks to translate and adapt a pregnancy app for an emerging Latino community - Anabel F. Castillo; Alexander L. Davis; Tamar Krishnamurti (BMC, 2022)
Abstract Background Digital mobile health (mHealth) applications are a popular form of prenatal education and care delivery in the U.S.; yet there are few Spanish language options for native speakers. Furthermore, existing applications do not consider cultural differences and disparities in healthcare access, including those specific to emerging Latino communities. Objective To adapt and translate an English-language pregnancy mobile health app to meet the language and cultural needs of Spanish-speaking Latino immigrants living in the United States. Methods We use a multi-step process, grounded in implementation science frameworks, to adapt and translate the contents of an existing pregnancy app. Interviews with stakeholders (n = 12) who advocate for the needs of pregnant individuals in an emerging Latino community were used to identify domains of possible disparities in access to prenatal care. We then conducted semi-structured interviews with peripartum Spanish-speaking Latino users (n = 14) to understand their perspectives within those domains. We identified a list of topics to create educational material for the modified app and implemented a systematic translation approach to ensure that the new version was acceptable for immigrants from different countries in Latin America. Results The interviews with stakeholders revealed seven critical domains that need to be addressed in an adapted prenatal app: language and communication, financial concerns, social support, immigration status, cultural differences, healthcare navigation, and connection to population-specific community resources that offer Spanish language services. The interviews with peripartum Spanish-speaking Latino women informed how the existing content in the app could be adjusted or built upon to address these issues, including providing information on accessing care offered in their native language and community support. Finally, we used a systematic approach to translate the existing application and create new content. Conclusion This work illustrates a process to adapt an mHealth pregnancy app to the needs of an emerging Latino community, by incorporating culturally sensitive Spanish language content while focusing on addressing existing health disparities.